Pengaruh Terapi Mewarnai Gambar Terhadap Tingkat Kecemasan Pada Anak Prasekolah Selama Hospitalisasi Di Ruang Jasmine Rs Yadika Kebayoran Jakarta Selatan Tahun 2022 - Riski Nadian Wardani; Marisca Agustina; Aisyah Safitri (The Journal General Health and Pharmaceutical Sciences Research, 2023)
School-age children who are undergoing hospitalization experience anxiety. One form of activity that can be done to reduce anxiety is through play therapy activities. Picture coloring therapy is one of the games that is in accordance with the principles of the hospital where psychologically this game can help children express feelings of anxiety, fear, sadness, depression and emotion. The purpose of the study was to determine the effect of Image Coloring Play Therapy on the Anxiety Level of Preschool Children During Hospitalization in the Jasmine Room of Rs Yadika Kebayoran Lama South Jakarta Year 2022. This study used a pre - experiment method with a one group pre - post - test design approach and purposive sampling technique with the number of samples to be given coloring therapy as many as 15 preschool children. The results of the study were conducted with a T-test which showed the effect of Picture Coloring Therapy on Anxiety Levels in Preschool Children During Hospitalization in the Jasmine Room of Rs Yadika Kebayoran Lama South Jakarta in 2022 obtained a P value of 0.001 smaller than 0.05 (0.001 <0.05).